Effect of subsidy regimes on economic values of functional traits in beef cattle breeding - Wolfová, Marie; Přibyl, Josef; Wolf, Jochen; Zahrádková, Radka (Journal of animal breeding and genetics, 2006)
We investigated the impact of five monetary subsidy regimes on economic values of traits in a cow-calf pasture production system with surplus calves fed for slaughter. The following regimes were analysed: (1) maximum prices for slaughter animals actually received in the Czech Republic during 2004, with no subsidies of any kind; (2) prices as in (1), with subsidies awarded per hectare of permanent grassland and per calf born; (3) prices as in (1), with subsidies awarded per hectare of agricultural land, per hectare of pasture and meadow, per beef cow in a forage system and per livestock unit; (4) prices as in (1), with subsidies awarded per hectare of agricultural land; (5) no subsidies, but prices received for slaughter animals that covered production costs and resulted in 1% profitability. The modelled farm showed negative profit under real price conditions with no subsidies (regime 1), which led to an underestimation of economic values for functional traits. The same results were obtained in regimes in which subsidies did not depend on the number of animals (3) or on meat production from the enterprise (4). Economic values of production traits (growth and carcass traits) did not vary among subsidy regimes. To determine optimum economic values for functional traits in beef cattle, we advocate using the method applied in subsidy regime 5, no subsidies but prices for slaughter animals that cover production cost and a small profit.
Keywords: Meat; Česká republika; maso; zvířata; Breeding; skot; Animals; Czech Republic; Models, Theoretical; Female; financování organizované; Male; ženské pohlaví; Animal Husbandry; mužské pohlaví; financování vládou; chov; chov zvířat; Cattle; Financing, Organized; teoretické modely; Financing, Government